IMPLEMENTASI KETERAMPILAN ABAD 21 DALAM KEGIATAN PEMBELAJARAN DI SDN CIPAYUNG 01 KABUPATEN BOGOR - Annisa Nahdiah; Sholeh Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This study aims to determine 21st century skills in learning activities. The 21st century skills in question include planning teaching materials, presenting problems, creating discussion groups, and making presentations. The activities carried out are project-based learning or project-based learning. This research was conducted from June to August 2022, at SDN Cipayung 01, Cibinong, Bogor District. The research design that the researcher uses is descriptive qualitative with the methods of interview, observation, and documentation. This study contains the activities of classroom teachers in providing action to students, especially in providing 21st century skills which require students to be ready to face challenges in the future.